2022
DOI: 10.1111/jcal.12770
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between problem‐solving behaviour and performance – Analysing tool use and information retrieval in a computer‐based office simulation

Abstract: Background: Problem-solving competences have evolved into key skills for professionals. Computer-based business simulations enable the analysis of problemsolving processes beyond end results. An important aspect of successful problemsolving is to systematically use built-in tools and process the provided information efficiently.Objectives: This investigation explores the relationship between students' tool use, information retrieval, and problem-solving success in a computerized problem-solving office simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
1
2
0
Order By: Relevance
“…Besides that, PBL can also help students to be active and independent in developing problem-solving thinking skills through searching data so that rational and authentic solutions are obtained [68]. This is in line with previous research that the PBL model helps to create an active learning atmosphere that involves students so that it is useful for fostering their self-confidence, increasing their thinking patterns, building their continuous knowledge of real-world problems, and using access tools to improve their problem-solving competences [62], [63]. The PBL model, in its implementation, provides opportunities for students to understand learning by solving problems given by the teacher by forming groups.…”
Section: Discussionsupporting
confidence: 74%
“…Besides that, PBL can also help students to be active and independent in developing problem-solving thinking skills through searching data so that rational and authentic solutions are obtained [68]. This is in line with previous research that the PBL model helps to create an active learning atmosphere that involves students so that it is useful for fostering their self-confidence, increasing their thinking patterns, building their continuous knowledge of real-world problems, and using access tools to improve their problem-solving competences [62], [63]. The PBL model, in its implementation, provides opportunities for students to understand learning by solving problems given by the teacher by forming groups.…”
Section: Discussionsupporting
confidence: 74%
“…For instance, Salles et al, (2020) showed that test takers who responded to a mathematical item with a graph correctly tended to use a digital pen for taking notes on the graph. Another study on computer based office simulation tests showed that successful test takers tended to use notepad and spreadsheets helping computation more efficiently (Ludwig & Rausch, 2022).…”
Section: Tool Use In Technology-enhanced Itemsmentioning
confidence: 99%
“…However, current applications of LA in PBL have not related LA results with specific PBL steps: Problem-solving performance and awareness were usually predicated by the overall LA without differentiation of the theoretical stages of PBL ( Chen et al, 2019 ; Ludwig and Rausch, 2022 ). Additionally, text data generated from peer interaction are not mined effectively by LA methods.…”
Section: Introductionmentioning
confidence: 99%